Identification of MicroRNAs Associated with Ileal and Colonic Crohn’s Disease - Wu, Feng (2010)
BACKGROUND: Crohn’s disease (CD) and ulcerative colitis (UC) are associated with expression differences in genes involved in immune function, wound healing, and tissue remodeling. Micro-RNAs (miRNAs) are small, noncoding RNAs that act as potent negative regulators of gene expression and are differentially expressed in chronic inflammatory diseases, including UC. We examined the expression of miRNAs in tissues from different intestinal regions and in patients with active ileal and colonic CD. METHODS: Colonoscopic pinch biopsies were obtained from the terminal ileum, cecum, transverse colon, sigmoid colon, and rectum of normal, healthy adults and from the ileum and sigmoid colon of patients with active ileal and colonic CD. miRNA expression was assessed using miRNA microarray and validated by mature miRNA quantitative reverse-transcription polymerase chain reaction (RT-PCR). RESULTS: Ten intestine region-specific miRNAs were identified. Three miRNAs were increased and one miRNA was decreased in the terminal ileum as compared to the colon. Six other miRNAs expressed varying levels of expression among the colon regions. Five miRNAs were found to be differentially expressed in tissues of patients with active colonic CD, with three increased and two decreased as compared to normal, healthy controls. Similarly, four miRNAs were found to be significantly increased in tissues of patients with active ileal CD. CONCLUSIONS: The expression differences between ileal CD, colonic CD, and previously identified UC-associated miRNAs support the likelihood that miRNAs influence differing inflammation-related gene expression in each inflammatory bowel disease (IBD) subtype and may form the basis for future diagnostic tests and therapeutic targets for IBD.